Organising for donor effectiveness: An analytical framework for improving aid effectiveness policies - Nilima Gulrajani (University of Oxford, Global Economic Governance Programme (GEG), 2013)
To what extent do donor organisational factors impinge on the search for more effective foreign aid? Donors have lagged behind aid recipients in adhering to the principles of aid effectiveness. Explaining the reasons for this demands greater awareness of organisational attributes within donor entities. Donor organisational features that have a credible positive impact on aid effectiveness are identified as the analytical components of donor effectiveness. To date, there have been limited attempts to relate donor organisational factors to aid effectiveness goals. This article elaborates on a number of such relationships based on an empirical examination of donor dynamics in Norway, the UK and Canada. Organisational features identified as contributors to aid effectiveness include a conducive political environment, a powerfully mandate ministry of development, a high-level policy statement on development and bounded professional discretion. Donor effectiveness provides an important lens through which to build a robust post-Busan global partnership.
Keywords: 330